Nathaniel Hawthorne - American Writers 23 : University of Minnesota Pamphlets on American Writers - Waggoner, Hyatt Howe (Book collections on Project MUSE., 1962)
Nathaniel Hawthorne - American Writers 23 was first published in 1962. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.